Patient-perceived effectiveness and impact on quality of life of solifenacin in combination with an α-blocker in men with overactive bladder in Sweden: a non-interventional study. (2nd October 2017) - Henningsohn, Lars; Kilany, Suzanne; Svensson, Maja; Jacobsen, Judith L.
Abstract: Treating male lower urinary tract symptoms (LUTS) by targeting the prostate would have limited effect on overactive bladder (OAB) symptoms. This study assessed perceived symptoms and quality of life (QoL) of male patients with OAB treated with an α-blocker plus solifenacin in daily clinical practice. Male patients aged ≥40 years were included after the decision was made to initiate treatment with an α-blocker for LUTS plus solifenacin for OAB symptoms. The primary endpoint was change in patient perception of bladder condition (PPBC) questionnaire score over 6 months. Other assessments included the OAB-questionnaire short form (OAB-q SF) and International Prostate Symptom Score (IPSS). Interpretation of the study data was hindered by not meeting the enrollment target and a high dropout rate. In 36 evaluable patients, mean (SD) PPBC score improved from 4.3 (0.93) at baseline ("moderate" to "severe" problems) to 3.5 (1.06) at month 6 ("minor" to "moderate" problems). OAB-q SF scores and total IPSS also improved. In this patient population, treatment with solifenacin and an α-blocker resulted in improvements in male patient perception of their LUTS and QoL, although the results should be interpreted with caution due to the low number of patients with complete data.